Mycelium-Bound composites from agro-industrial waste for broadband acoustic absorption - Wenjing Sun; Sophie H. Strässle Zúñiga; Valentin Philippe; Louisa Rinaldi; Tiffany Abitbol (Materials & Design)
This research explores the development of mycelium-bound composites for acoustic applications where natural fungal mycelia is used to bind organic waste into sound absorbing panels. The composites were grown in 3D printed molds to impart precise perforated patterns according to the principles of Helmholtz resonance. This approach led to improvements in sound absorption across a broad frequency range, particularly at low to mid-frequencies. By using agro-industrial waste as the raw material, our approach demonstrates the potential for upcycling while maintaining an entirely biodegradable composition. The study highlights the flexibility in material composition and design, offering a pathway for further refinements to optimize acoustic performance.